“I,” “Unknown”: Female Subjectivity in Miriam Waddington’s Early Life Writing and Green World (1945) - McLauchlan, Laura (Canadian Jewish Studies / Études juives canadiennes, 2003)
This essay examines the early life writing and poetry of Miriam Waddington with the goal of contributing to a reevaluation of second wave Canadian modernism. More specifically, it uses journals, unpublished poems, and Waddington’s Master’s thesis (in Social Work) as a means of contextualizing the “inner underground life” of a writer who is both Jewish and female. In doing so, this essay has two purposes: the first is to offer an account of the material relevant to this study found in the early unpublished material in the Waddington Papers held in Library and Archives Canada, and second, to explore female subjectivity in both the unpublished life writing and in Green World.